Chile: o golpe estético como estratégia do domínio de corações e mentes (1970’s) - Chélest, Alessandra Di Giorgi (2023)
By analyzing the Chilean case, the research investigates how a given aesthetic logic was inculcated and disseminated throughout the dictatorship which ravaged that country. This logic, pointed out by some authors as a low-intensity war strategy, in other words, one that uses covert and sublinear actions, concomitantly with the violence inherent in the formal methods of any war. Such operations, also emanating from the guidelines of the national security doctrines, aimed to reach subjectivities with the purpose of transmuting the minds and psyche that are part of the social substrate, in favor of the ideology propagated by the dictatorship. Through the analyzed sources, audiovisual materials, and complementary documentation, we sought to understand how changes were promoted in the sensibilities that made up the signs, symbols, and immanent representations of social relations which integrate the culture of a people. Aside from the techniques used by mass communication strategists, they proceeded to inculcate what we call an aesthetic coup. For, in addition to forming a public opinion favorable to the dictatorship, efforts were made to erase, from the collective substratum, the ideals in search of a more just and egalitarian society, eliminating the hope that would generate resistance, and transmuting the senses and meanings of symbols and signs. By doing so, they aimed to obtain greater social control in order to establish the rooting of individualism, competitive relationships as opposed to solidarity, and the intensification of the commodification of personal relationships, namely, the precepts of neoliberalism